Prevalence and risk factors associated with Dirofilaria immitis infection in dogs and cats in Songkhla and Satun provinces, Thailand - Kamyingkird, Ketsarin; Junsiri, Witchuta; Chimnoi, Witsanuwat; Kengradomkij, Chanya; Saengow, Sinsamut; Sangchuto, Keplee; Kajeerum, Wicha; Pangjai, Decha; Nimsuphan, Burin; Inpankeaw, Tawin; Jittapalapong, Sathaporn (Agriculture and Natural Resources, 2017)
To update the microfilaria infection in companion animals, this study determined the prevalence and risk factors of microfilaria infection in dogs and cats collected from eight districts in Songkhla and Satun provinces, southern Thailand. In total, 482 samples (394 dogs and 88 cats) were subjected to microscopic examination (ME), polymerase chain reaction (PCR) and sequencing analysis. The overall prevalence of microfilaria infection in dogs and cats was 24.1% (95/394) and 36.4% (32/88) using PCR, respectively. Furthermore, the overall results were positive 7.7% (37/482) using ME compared to 26.3% (127/482) using PCR. Sequencing analysis of all positive PCR products identified the microfilaria as Dirofilaria immitis. D. immitis infection in each sampled district of Songkhla and Satun provinces was in the range 0-48% for dogs and in the range 15.4-75% for cats. Risk factor analysis showed that there was significantly higher D. immitis infection in dogs older than 2 yr. The study updated the prevalence of D. immitis infection in dogs and cats in two southern provinces of Thailand and there was a high D. immitis infection rate in old dogs (aged > 2 yr).